Factors associated with glycemic control in people with diabetes at the Family Health Strategy in Pernambuco - Rodrigo Fonseca Lima; Annick Fontbonne; Eduardo Maia Freese de Carvalho; Ulisses Ramos Montarroyos; Maria Nelly Sobreira de Carvalho Barreto; Eduarda Ângela Pessoa Cesse
Abstract OBJECTIVE Identifying factors associated with glycemic control in people with type 2 Diabetes Mellitus (DM) registered in the Family Health Strategy (FHS) in Pernambuco, Brazil. METHOD Associations between glycemic control (glycosylated hemoglobin A lower or equal to 7%) presented by people with DM and variables related to sociodemographic conditions, lifestyle, characteristics of diabetes, treatment and follow-up of patients by health services were investigated by multiple regression. RESULTS More than 65% of the participants presented inadequate glycemic control, especially those with lower age, longer illness duration, more annual contacts with FHS and complex therapeutic regimen. People with DM without referrals to specialists presented greater glycemic control. Associations with education level and obesity did not remain significant in the multivariate model. CONCLUSION The evolution of diabetes hinders adequate control, however, attention to younger people with DM and referrals to specialists are factors that can improve glycemic control.